2020
DOI: 10.7150/ijms.45706
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H:quinone oxidoreductase 1 determines radiosensitivity of triple negative breast cancer cells and is controlled by long non-coding RNA NEAT1

Abstract: Radioresistant cells cause recurrence in patients with breast cancer after they undergo radiation therapy. The molecular mechanisms by which cancer cells obtain radioresistance should be understood to develop radiation-sensitizing agents. Results showed that the protein expression and activity of NAD(P)H:quinone oxidoreductase 1 (NQO1) were upregulated in radioresistant MDA-MB-231 triple-negative breast cancer (TNBC) cells. NQO1 knockdown inhibited the proliferation of NQO1 expressing Hs578t TNBC cells or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…However, it was interesting to note that the radioresistant phenotype in NF639R cells was still maintained after 30 passages. In fact, some researchers observed that 40 Gy irradiation is enough to induce radioresistance in some breast cancer cells such as MCF7 and MDA-MB-231 (43,44). However, radioresistant cells established by 40 Gy or less total dose radiation may be instable due to transient genetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was interesting to note that the radioresistant phenotype in NF639R cells was still maintained after 30 passages. In fact, some researchers observed that 40 Gy irradiation is enough to induce radioresistance in some breast cancer cells such as MCF7 and MDA-MB-231 (43,44). However, radioresistant cells established by 40 Gy or less total dose radiation may be instable due to transient genetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…51 Recently, Lin et al described the role of NEAT1 in regulating radioresistance by targeting NAD(P)H:quinone oxidoreductase 1 (NQO1). 52 They showed the positive regulation of NQO1 by NEAT1 at the translational level in radioresistant triple negative breast cancer cells. By inhibiting NEAT1, they were able to trigger oxidative stress and increase the radiosensitivity of the cells, 52 giving a potential treatment strategy for resistant cancer phenotypes.…”
Section: Lncrnas In Radiation Responsementioning
confidence: 99%
“…Inhibition of NEAT1 expression by CRISPR-Cas9 increases the sensitivity of radiation-resistant cells to radiation and reduces cell proliferation and the expression of tumor stem cell markers including BMI1, OCT4, and SOX2. 271 In addition, MEG3 knockout mediated by the CRISPR-Cas9 system significantly reduces the invasion ability of human triple-negative metastatic Hs578T cancer cells. 215 These evidences suggest that CRISPR-Cas9 genome editing can be used to precisely eliminate abnormally expressed lncRNAs in cancer cells, thereby providing a useful strategy to target oncogenes for the development of novel precision medicine therapies.…”
Section: Lncrnas As Biomarkers and Therapeutic Targets For Breast Cancermentioning
confidence: 99%